P132 Uncovering blood biomarkers of Inflammatory Bowel Diseases by Raman spectroscopy and FAP dosage: toward a noninvasive triage of patients in first care diagnostic. (27th May 2021) - Truffi, M; Morasso, C; Albasini, S; Malovini, A; Bellazzi, R; Piccotti, F; Caldarone, A; Sorrentino, L; Mazzucchelli, S; Sampietro, G; Colombo, F; Ardizzone, S; et al.
Abstract: Background: Currently, a major point of concern in the management of Inflammatory Bowel Diseases (IBD) is the absence of accurate and specific circulating biomarkers able to drive diagnosis in a timely and noninvasive manner. Aim of the present study was to explore blood biomarkers of IBD by coupling the targeted detection of circulating fibroblast activation protein (FAP), a recognized valuable marker of bowel lesion in IBD, and Raman spectroscopy (RS), a quick and label-free metabolomic technique that provides a real-time biochemical characterization of plasma samples without any previously known target. Methods: Blood samples were collected from over 140 patients with IBD and 170 control subjects matched for gender and age. Isolated plasma was analysed by enzyme-linked immunosorbent assay for quantitative detection of circulating form of FAP. RS was performed on dry droplets of plasma, with the aim to decipher specific fingerprint of IBD in peripheral blood. A predictive model was built on FAP and Raman data separately, to determine specificity, sensitivity and accuracy of the two approaches in patients classification. Supervised multivariate model was applied on a subset of 203 patients to discriminate IBD and control subjects based on combined datasets. Results: FAP levels were reduced in patients with IBD as compared to controls (p<0.0001). The sensitivity and specificity of FAP were 70% and 84% based on the optimal cutoff (57.6 ng mL -1, AUC=0.78). Raman spectra of IBD plasma revealed significant differences in peaks corresponding to carotenoids, proteins with β-sheet secondary structure, lipids and aromatic amino-acids. A machine learning model was applied on a subset of patients reaching an accuracy of 85% in classifying IBD and control subjects. No statistically significant differences were observed so far between the discriminative performance of the sole RS or the combination of RS and FAP. Conclusion: RS and FAP dosage enable new discoveries in the biological fingerprint of IBD plasma and provide novel candidate biomarkers of IBD. Our preliminary results strongly suggest that novel blood-based approaches could represent a fast noninvasive way to triage patents with suspected IBD in first care diagnostic, to be applied prior to further specific evaluation.